Transient immunological control during acute hepatitis C virus infection: ex vivo analysis of helper T-cell responses. - Ulsenheimer, A; Lucas, M; Seth, N; Tilman Gerlach, J; Gruener, N; Loughry, A; Pape, G; Wucherpfennig, K; Diepolder, H; Klenerman, P (2006)
Hepatitis C virus (HCV) readily sets up persistence after acute infection. Cellular immune responses are thought to play a major role in control of the virus. Failure of CD4+ T-cell responses in acute disease is associated with viral persistence but the dynamics of this are poorly understood. We aimed to assess such responses using a novel set of Class II tetrameric complexes (tetramers) to study helper T-cells ex vivo in acute disease. We analysed the HCV-specific CD4+ T-cell response in a patient with acute hepatitis c infection. We were able to track the virus-specific CD4+ T-cells directly ex vivo with HLA DR4 tetramers. Proliferative responses were absent initially, recovered as viral load dropped and were lost again during relapse. Longitudinal tetramer analyses showed expanded populations of antiviral CD4+ T-cells throughout acute infection despite lack of proliferation. A pattern of transient CD4+ T-cell proliferative responses as HCV is partially controlled is observed. Failure to control virus is associated with emergence of 'dysfunctional' CD4+ T-cell populations. Failure to control HCV in acute disease may relate to the capacity to sustain efficient immune responses as virus attempts to 'bounce back' after partial control.